2020
DOI: 10.1101/2020.04.29.20083808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of high intensity interval exercise on cerebrovascular function: A systematic review

Abstract: High intensity interval exercise (HIIE) improves aerobic fitness with decreased exercise time compared to moderate continuous exercise. A gap in knowledge exists regarding the effects of HIIE on cerebrovascular function such as cerebral blood velocity and autoregulation. The objective of this systematic review was to ascertain the effect of HIIE on cerebrovascular function in healthy individuals. We searched PubMed and the Cumulative Index to Nursing and Allied Health Literature databases with apriori key word… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Cardiovascular hemodynamic load dramatically increases with strenuous exercise bouts, challenging CBF regulation. CBF usually increases after short‐term and moderate exercise but decreases as exercise time and intensity increase, thereby attenuating dynamic cerebral autoregulation 64 . Whether a decrease in CBF due to strenuous exercise results in brain oxygenation abnormalities remains disputed, 65 with some reports indicating that oxygen delivery to the mitochondria might be compromised 66 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular hemodynamic load dramatically increases with strenuous exercise bouts, challenging CBF regulation. CBF usually increases after short‐term and moderate exercise but decreases as exercise time and intensity increase, thereby attenuating dynamic cerebral autoregulation 64 . Whether a decrease in CBF due to strenuous exercise results in brain oxygenation abnormalities remains disputed, 65 with some reports indicating that oxygen delivery to the mitochondria might be compromised 66 .…”
Section: Discussionmentioning
confidence: 99%
“…CBF usually increases after short-term and moderate exercise but decreases as exercise time and intensity increase, thereby attenuating dynamic cerebral autoregulation. 64 Whether a decrease in CBF due to strenuous exercise results in brain oxygenation abnormalities remains disputed, 65 with some reports indicating that oxygen delivery to the mitochondria might be compromised. 66 These acute effects on CBF may be augmented by the stiffening of large arteries 67 that is suggested to occur after long-term strenuous training.…”
Section: Moderate and Intense Exercise Bouts Elicit Different Hemodyn...mentioning
confidence: 99%
“…In regards to the impact of HIIT on P ET CO 2 and cerebrovascular reactivity to CO 2 , the literature is scarce. According to a systematic review by Whitaker et al (Whitaker et al, 2020), only one study has reported the chronic effect of HIIT on cerebrovascular reactivity to CO 2 . In that study, 12 weeks of HIIT did not influence cerebrovascular reactivity to CO 2 in breast cancer survivors.…”
Section: Influence Of P Et Co 2 and Cerebrovascular Reactivity To Co ...mentioning
confidence: 99%
“…Extensive research has been conducted on HIIT, indicating its relevance in clinical and physiological research with improvements in cardiorespiratory fitness beyond moderate‐intensity continuous training (Calverley et al, 2020; MacInnis & Gibala, 2017; Weston et al, 2014). Although HIIT presents an interesting stimulus for the cardiovascular system, a limited number of studies have focused on its effects on the cerebrovascular system (reviewed in Whitaker et al, 2020). Indeed, recent work by Whitaker et al indicated more research is needed to confirm the acute (Whitaker et al, 2022) and chronic (Whitaker et al, 2020) effects of HIIT on the cerebrovascular function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation